Evaluation of Further Training Programmes in Saxony from 1989 to 2001 - Eva Reinowski; Birgit Schultz; Jürgen Wiemers (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2004)
This study evaluates the effects of further training on the individual unemployment duration of different groups of persons representing individual characteristics and some aspects of the economic environment. The Micro Census Saxony enables us to include additional information about a person's employment history to eliminate the bias resulting from unobservable characteristics and to avoid Ashenfelter's Dip. To solve the sample selection problem we employ an optimal full matching assignment, the Hungarian algorithm, using an aggregate distance measure. This procedure is superior to greedy pair matching in the sense that it avoids the loss of observations due to the design of the algorithm and yields the optimal assignment result, i.e. the minimum total sum of squared distances. The impact of participation in further training is evaluated by comparing the unemployment duration between participants and non-participants using the Cox Proportional Hazard Model. Overall, we find empirical evidence that participation in further training programmes results in even longer unemployment duration – with only gradual differences in the analysed groups.
Keywords: C14; C41; H43; J68; 330; Evaluation; Further Training; Optimal Full Matching; Duration Analysis